Liquid‐Metal‐Assisted Synthesis of Single‐Crystalline TiC Nanocubes with Exposed {100} Facets for Enhanced Electrocatalytic Activity in the Hydrogen Evolution Reaction (Small Methods 1/2023). Issue 1 (17th January 2023) - Jeong, Kyoung‐Jin; Lee, Yohan; Huynh, Thanh‐Nam; Nersisyan, Hayk; Suh, Hoyoung; Lee, JongHyeon
Abstract : Back Cover In article number 2201076, Lee and co‐workers used the combustion synthesis method to grow single‐crystalline TiC nanocubes with exposed (100) facets in liquid Mg medium for the first time. They then validated the formation mechanism using the density functional theory method and evaluated the electrocatalytic performance for the hydrogen evaluation reaction from water.